The effect of glucoregulation on hearing loss in patients with diabetes mellitus type 2 - Mirjana Gnjatić; Dalibor Vranješ; Tamara Dojčinović; Jelena Malinović Pančić; Boris Dojčinović (Биомедицинска истраживања, 2024)
Introduction: Hyperglycemia causes the well-known microvascular complications of diabetes mellitus (DM) such as diabetic retinopathy, polyneuropathy and nephropathy, but it can also affect the inner ear, and hearing loss (HL) can be considered as one of the microvascular complications. The aim of the study was to evaluate association between HL and values of glycated hemoglobin A1c (HbA1c) in patients with diabetes mellitus type 2 (DMT2). Methods: In this retrospective-observational cross sectional study, we included 80 patients divided into two groups: experimental group consisting of 40 patients with DMT2 and control group consisting of 40 patients who were not previously diagnosed with DM. Data were retrieved from electronic medical records of patients treated in outpatient clinic of the Ear, Nose and Throat Department, University clinical center of Republic of Srpska (UCC RS) from 2023 to 2024. Results: Out of 40 patients from experimental group, 15 were males (37.5%) and 25 were females (62.5%). Regarding glycoregulation patterns in experimental group, patients were stratified into three subgroups: HbA1c < 7% (N 17; 42.5%), HbA1c-9% (N 17; 42.5%) and HbA1c > 9% (N 6; 15%). In the experimental group, a significant (p<0.000) greater number of patients had HL, and significant greater number of patients had bilateral HL (N 32; 80%, p<0.05) with predominantly pronounced sensorineural HL (N 36; 90%, p<0.05). Conclusion: Patients with DMT2 had a higher incidence of HL compared to controls. The sensorineural type of HL showed a significantly high prevalence among patients with DMT2. HbA1c levels may be a potentially significant predictor of HL in DMT2.
Keywords: diabetes mellitus; hearing loss; pure tone average